Thinking Across Hemispheres: Further notes on Oversights and Blind Spots in Disciplinary African Studies - Lalu, Premesh (Afrika Focus, 2019)
In the midst of ever-hardening nationalist sentiment across the world, the humanities may need to recall its long history of thinking across hemispheres. In such balkanised times, we may have to rethink the work that a hermeneutics of suspicion performs for a critical humanities as well as how Africa is bound to particular configurations of area studies that emerge out of the geopolitical distributions of knowledge during the Cold War. To the extent that we might develop a history of a critical humanities across hemispheres, this paper asks what it might mean to return to a concept of freedom formed through a sustained effort at reckoning with the worldliness specific to the anti- colonial struggles in Africa. There, a critical humanities may discover the sources of a creative work in which Africa is not merely bound to the binary of blind spots and oversights, but functions as that supplement which gives itself over to a liveable future.